2013
DOI: 10.1017/s0142716413000222
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of morphological awareness and processing in adults with low literacy

Abstract: Morphological awareness, which is an understanding of how words can be broken down into smaller units of meaning such as roots, prefixes, and suffixes, has emerged as an important contributor to word reading and comprehension skills. The first aim of the current study was to investigate the contribution of morphological awareness independent of phonological awareness and decoding to the reading comprehension abilities of adults with low literacy. Results indicated that morphological awareness was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
70
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 43 publications
8
70
0
5
Order By: Relevance
“…Morphological awareness had the strongest relationship with reading comprehension ( r = .59) and was significantly more related to reading comprehension than phonological awareness ( r = .34) and RAN ( r = .15). This finding is consistent with Tighe and Binder (2014) who reported that morphological awareness accounted for an additional 37% of the reading comprehension variance after controlling for phonological awareness. However, we were unable to determine significance among morphological awareness and orthographic knowledge as well as phonological awareness and orthographic knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Morphological awareness had the strongest relationship with reading comprehension ( r = .59) and was significantly more related to reading comprehension than phonological awareness ( r = .34) and RAN ( r = .15). This finding is consistent with Tighe and Binder (2014) who reported that morphological awareness accounted for an additional 37% of the reading comprehension variance after controlling for phonological awareness. However, we were unable to determine significance among morphological awareness and orthographic knowledge as well as phonological awareness and orthographic knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…None of the research has investigated the unique and shared contributions of all three metalinguistic skills to reading skills; however, these constructs have been considered separately (or included two of the constructs) across several studies. For example, three recent studies have reported that morphological awareness is an important predictor of ABE students’ reading comprehension skills after controlling for phonological awareness (Tighe & Binder, 2014), decoding (To et al, in press), and oral vocabulary knowledge (Tighe, 2012). Phonological awareness has been reported as an important predictor of reading comprehension (Thompkins & Binder, 2003; Tighe & Binder, 2014), word reading skills (Greenberg, Ehri, & Perin, 1997) and a composite score of word reading, fluency, and comprehension skills (Binder et al, 2011).…”
Section: Metalinguistic Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding supports the notion that morphological awareness contributes to reading comprehension by aiding vocabulary, since the best predictor of vocabulary was morphological awareness (Keiffer, 2009; Nagy et al, 2006). In the current study, when vocabulary was not entered into the regression model, morphological awareness was a significant predictor of comprehension, and this finding is consistent with Tighe and Binder (2014), which was the first study to document the role of morphological awareness in reading comprehension for adults who were enrolled in ABE programs. Our finding further supports previous research that morphological awareness does aid comprehension through vocabulary (Fowler & Liberman, 1995; Kuo & Anderson, 2006; McBride-Chang et al, 2008; Shankweiler et al, 1995).…”
Section: Discussionsupporting
confidence: 86%